The diagnosis and treatment of isolated type B fibular fractures: Results of a nationwide survey. Issue 2 (February 2019) - van Leeuwen, C.A.T.; Hoffman, R.P.C.; Donken, C.C.M.A.; van der Plaat, L.W.; Schepers, T.; Hoogendoorn, J.M.
Highlights: The recently published Dutch protocol advises to make use of additional diagnostics in case of MCS < 6 mm. Most Dutch surgeons are not aware of this protocol and do not make use of it. Most Dutch surgeons treat type B fibula fractures surgically, even with no proven medial injury. This will lead to unnecessary surgery. There is no consensus in treatment nor diagnostics of type B fibula fractures in the Netherlands. The current protocol is not being followed. Abstract: Introduction: In isolated Weber B fractures (type B fibular fractures), ruling out instability is critical for safe conservative treatment. In fractures without evident medial injury, additional diagnostics like MRI scan or gravity stress test should be done to differentiate between a stable and unstable fracture. The aim of the current study is to gain more insight in current practice and treatment of type B fractures by Dutch trauma- and orthopaedic surgeons. Materials & methods: In December 2017 and January 2018, 559 trauma surgeons were invited by email to join an online survey. This survey consisted of questions regarding diagnostics and treatment of isolated distal fibula fractures. Also, respondents were asked to state their preferred treatment of eight separate cases. Results: In total, 161 surgeons participated, covering 68 different hospitals in the Netherlands. Of them, 32.0% treat more than 30 ankle fractures a year. Based on regular mortise radiographs, 13.6% of the respondents chose surgical treatment in case of a medial clear space (MCS) > 4 mm, 33.8% in case of a MCS > 6 mm and 45.5% in case of a MCS > 4 mm in addition to the MCS ≥ superior clear space + 1 mm. Moreover, 18.2% make use of additional diagnostics (43.9% repeat mortise view after a week, 16.6% weight bearing radiograph, 8.6% gravity stress view, 7.9% exorotation radiograph, 6.5% MRI scan, 0.7% ultrasound, 16.8% other) and 8% establishes their decision not based on the mortise radiograph. Fibular dislocation of ≥ 2 mm was used as an indication for surgical treatment by 69%. Of them, 56% decides to treat surgically in these cases, even with proven medial stability. Conclusion: Many surgeons treat type B fibular fractures with a MCS > 4 mm at mortise view surgically, even without proven medial injury. Rarely, additional diagnostics as MRI or gravity stress test are performed in cases with a MCS 4–6 mm. Consequently many stable ankle fractures are treated operatively unnecessarily.